Cognitive-behavioral determinants of using helmet by motorcyclists in a rural community. (September 2017) - Ghasemzadeh, Sadegh; Babazadeh, Towhid; Allahverdipour, Hamid; Sadeghi-Bazargani, Homayoun; Kouzekanani, Kamiar
Abstract: Background: Wearing a helmet while riding a motorcycle is influenced by various factors such as the existing traffic rules, environmental factors, law enforcement by the police, social norms, and the community's common beliefs. The purpose of this study was to identify the cognitive-behavioral factors of not using helmet in a rural community and to investigate whether the Theory of Planned Behavior (TPB) could predict not wearing helmets by motorcyclists. Methods: The sample for this cross-sectional study consisted of 150 motorcyclists. The setting was a rural community in Charoymag, located in North-West of Iran. A written questionnaire, interviews, and personal observations were used to collect the data. Two types of modeling approaches, general SEM and multi-groups SEM, were used to address the specific aims of study based on the theory of planned behavior. Results: Approximately, 47% of the motorcyclists did not wear helmets during the prior 30 days and only 8% stated that they always used a helmet while riding. Subjective norms supporting the use of helmets (p<0.001) and perceived behavioral control (p<0.001) were the statistically significant predictors of wearing helmets. Perceived behavioral control (p=0.14), positive attitudes towards wearing helmet (p=0.86), and subjective norms in support of using helmet (p=0.33) were not statistically significant in predicting the intention to wear the helmet in the near future. Additionally, intention to wear helmet could not predict wearing helmet in this study. Conclusions: Perceived behavioral control and social norms can be influential in using the helmet in a traditional rural setting, which can be used in planning head injury prevention programs for motorcyclists in rural communities. Highlights: 47% of the motorcyclists did not wear helmet during the prior 30 days. Theory of Planned Behavior may help explain helmet use among rural motorcyclists. Perceived behavioral control and social norms are important in using the helmet. Intention in the habitual behaviors might not predict behavior.